Copper resistance is essential for virulence of Mycobacterium tuberculosis - Wolschendorf, Frank (National Academy of Sciences, 2011)
Copper (Cu) is essential for many biological processes, but is toxic when present in excessive amounts. In this study, we provide evidence that Cu plays a crucial role in controlling tuberculosis. A Mycobacterium tuberculosis (Mtb) mutant lacking the outer membrane channel protein Rv1698 accumulated 100-fold more Cu and was more susceptible to Cu toxicity than WT Mtb. Similar phenotypes were observed for a M. smegmatis mutant lacking the homolog Ms3747, demonstrating that these mycobacterial copper transport proteins B (MctB) are essential for Cu resistance and maintenance of low intracellular Cu levels. Guinea pigs responded to infection with Mtb by increasing the Cu concentration in lung lesions. Loss of MctB resulted in a 1,000- and 100-fold reduced bacterial burden in lungs and lymph nodes, respectively, in guinea pigs infected with Mtb. In mice, the persistence defect of the Mtb mctB mutant was exacerbated by the addition of Cu to the diet. These experiments provide evidence that Cu is used by the mammalian host to control Mtb infection and that Cu resistance mechanisms are crucial for Mtb virulence. Importantly, Mtb is much more susceptible to Cu than other bacteria and is killed in vitro by Cu concentrations lower than those found in phagosomes of macrophages. Hence, this study reveals an Achilles heel of Mtb that might be a promising target for tuberculosis chemotherapy.